2021
DOI: 10.1093/geront/gnab078
|View full text |Cite
|
Sign up to set email alerts
|

The Lived Experience of Already-Lonely Older Adults During COVID-19

Abstract: Background and Objectives From the outset of the COVID-19 pandemic, analysts warned that older populations, due to their age, chronic illnesses, and lack of technological facility, would suffer disproportionately from loneliness as they sheltered in place indefinitely. Several studies have recently been published on the impact of COVID-19-related loneliness among older populations, but little has been written about the experiences of already-lonely older individuals; those that had lived with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 52 publications
3
37
0
1
Order By: Relevance
“…Socalled "kinless" older adults (unpartnered childless) were not necessarily at higher risk of loneliness during the pandemic than each group separately. This finding may reflect and support qualitatively the resilience of "already lonely" older adults (Bundy et al, 2021) such that "kinless" older adults potentially have long-standing resources and preparations (psychological, emotional, and instrumental) to cope with limited social resources and thus manage loneliness due to the absence of these traditional family resources. Additionally, "kinless" and childless older adults, whose networks are more friend-based (Mair, 2019), may have reduced their expectations for in-person social contacts thereby reducing their discrepancy in desired versus actual interactions and subsequent likelihood of becoming lonely during the pandemic (Dahlberg, 2021).…”
Section: Pandemic Loneliness Especially For Unpartnered and Childlessmentioning
confidence: 64%
See 2 more Smart Citations
“…Socalled "kinless" older adults (unpartnered childless) were not necessarily at higher risk of loneliness during the pandemic than each group separately. This finding may reflect and support qualitatively the resilience of "already lonely" older adults (Bundy et al, 2021) such that "kinless" older adults potentially have long-standing resources and preparations (psychological, emotional, and instrumental) to cope with limited social resources and thus manage loneliness due to the absence of these traditional family resources. Additionally, "kinless" and childless older adults, whose networks are more friend-based (Mair, 2019), may have reduced their expectations for in-person social contacts thereby reducing their discrepancy in desired versus actual interactions and subsequent likelihood of becoming lonely during the pandemic (Dahlberg, 2021).…”
Section: Pandemic Loneliness Especially For Unpartnered and Childlessmentioning
confidence: 64%
“…For example, Choi et al (2021) found that US older adults who limited social interactions during the early stages of the pandemic (April to May 2020) were at higher risk for loneliness, but Luchetti et al (2020) found no sustained increase of loneliness among older Americans (Luchetti et al, 2020). A qualitative US study found that older people who had lived with persistent loneliness before the pandemic did not report feeling lonelier than before COVID-19 (Bundy et al, 2021). Killgore et al (2020) and Sutton et al (2020) debated, via letters to the editor, the conflicting findings in online samples regarding American older adults' experienced loneliness increases during COVID-19.…”
Section: Older Adults' Loneliness During Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…All these variables were reported at the county-level and were selected based on the aforementioned comprehensive reviews and research reports ( Baltrus et al, 2021 ; Carter et al, 2014 ; Gundersen & Ziliak, 2018 ; Harris et al, 2014 ; Heid et al, 2021 ; Wu et al, 2020 ). That is, current research has found these socio-ecological factors explicate mortality for the coronavirus ( Bundy et al, 2021 ; Chiou and Tucker, 2020 ; Figueroa et al, 2020 , 2021 ; Lu et al, 2021 ; Russette et al, 2021 ; Wang et al, 2020 ; Williamson et al, 2020 ; see Supplementary Material for additional clarification about variables).…”
Section: Methodsmentioning
confidence: 98%
“…And it is important to make this qualification because, against expectations, several large-scale studies have shown that social isolation and stay-at-home orders did not necessarily result in an increase in loneliness for already-lonely older adults who were living independently, or if loneliness did increase, it did not adversely affect mental health as it did children and younger and middle-aged adults. (Bundy et al, 2021 ; Benke et al, 2020 ; Heidinger & Richter 2020 ; Kotwal et al, 2021 ; Lind et al, 2021 ) But this unexpected resilience among the elderly did not manifest for those restricted to nursing homes and other residential facilities. Confined in their rooms for months at a time, reports emerged of a distress that escalated dramatically, with residents becoming noticeably apathetic and listless, losing interest in eating and bathing, sleeping most of the day, and becoming indifferent to the idea of living altogether.…”
mentioning
confidence: 99%